Analisis Kerusakan Jalan dengan Metode Bina Marga dan Respon Pengguna Jalan terhadap Perbaikannya (Studi Kasus Ruas Jalan Jurong Bonai Darussalam) - saleh*, alfian; Muzki, Deni; Winayati (JURNAL TEKNIK, 2024)
Jurong road is a road which is located in Bonai Darussalam District, Rokan Hulu province. It is a road of 111 km (11 mi) long, and 6 m (20 ft) wide, it is a road leading to the pangararsand, where large cars often drive. Across the jurong road line, a vast range of road damage was found, at exactly 1, ooo to 1, ooo. The purpose in this study is to know the rate of road damage, and the effect of road damage on road use on jurong street, bonai darussalam district, upper rokan district, (sta 16+000 to sta 18+000) using clan building methods. Got results from jurong road damage survey with the kinds of cracked crocodile skin, buckskin, and holes. From the results of the damage analysis using clan building methods, results from the rate of damage or priority order (up) value are 9 which means that jurong street belongs to the regular maintenance category. And the results of the jurong road damage survey analysis using a likert scale method with a total of 50 respondents found at a percentage increase of 83,68 %, and based on the assessment interval of road conditions according to clan building values, it is between 80% % - 100 %, indicating that road damage is important to road users and that people are more than willing to make road improvements